ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SAAT PANDEMI COVID-19 PADA SUB SEKTOR HOTEL YANG TERDAFTAR DI BURSA EFEK INDONESIA 2019-2020 - Anang Anang; Hesti Setiorini; Marini Marini (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
The purpose of this study is to find out 1) the companies' financial performance seen from the profitability ratio using the calculation of return on assets, 2) the companies' financial performance seen from the liquidity ratio using the calculation of the current ratio, 3) the companies' financial performance seen from the solvency ratio using the debt to calculation equity ratio, 3) companies' financial performance seen from the activity ratio using asset turnover calculation. This research was conducted on hotel sector companies listed on the Indonesia Stock Exchange for the 2019-2020 period from 2 January 2023 to 2 February 2023. The hotel companies studied consisted of 21 companies with the 2019-2020 observation period so that the sample became 42 financial reports using the purposive sampling technique. The data collection techniques were in the form of documentation of financial reports. The data was analyzed using the descriptive quantitative by testing the Wilcoxon signed rank test. The results show that there are significant differences in financial performance before and during the Covid- 19 pandemic for the hotel sub-sector companies listed on the IDX in 2019-2020 with an Asymp value. Sig (2-tailed) on the variable return on assets 0.009 <0.05; at variable current ratio 0.021 <0.05; debt to equity ratio (DER) of 0.058> 0.05; total asset turnover (TATO) of 0.001 <0.05. Keywords:  Return On Assets, Current Ratio, Debt To Equity Ratio, Total Asset Turn Over